2019
DOI: 10.3390/polym11091429
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Deformation under Tension on Some Mechanical and Tribological Properties of High-Density Polyethylene

Abstract: Polymer materials are increasingly being used for sliding machine elements due to their numerous advantages. They are used even where they are deformed and in such a state that they interact frictionally, e.g., in machine hydraulics or lip seals. Few publications deal with the influence of deformation, which is the effect of, e.g., assembly on tribological properties of polymeric material. This deformation can reach up to ε ≈ 20% and is achieved without increasing the temperature of the polymer material. The p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Through control of the hydraulic systems, the movement and loads of the tested cylinder were realized. Hydraulic parameters were measured using pressure transducers (7,8) and a flow rate meter. The movement of the piston rod was monitored using a displacement transducer (9) and the force on the piston rod using a sensor located in the connector (4).…”
Section: Research Stand and Methods Of Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…Through control of the hydraulic systems, the movement and loads of the tested cylinder were realized. Hydraulic parameters were measured using pressure transducers (7,8) and a flow rate meter. The movement of the piston rod was monitored using a displacement transducer (9) and the force on the piston rod using a sensor located in the connector (4).…”
Section: Research Stand and Methods Of Testingmentioning
confidence: 99%
“…In this method, it was shown that the choice of plastic material has an impact on the design, manufacturing technology, exploitation and application areas of cylinders made of plastics. This is due to the lower strength and greater elasticity of plastic compared to metal materials [7]. Less strength and greater elasticity leads to greater deformations.…”
Section: Introductionmentioning
confidence: 99%
“…Plastics are widely used in the design of machine components (Skowrońska et al, 2021). Their satisfactory mechanical properties, combined with good tribological properties, self-lubrication and the possibility of modifying the composition, allow them to be used in elements such as gears, pumps and others (Chihai et al, 2019;Krawczyk, 2021;Kujawa et al, 2019;Li et al, 2021;Majdič & Strmčnik, 2019;Zhang et al, 2021). Manufacturing large sliding surfaces, such as the inner surface of a cylinder, from thermoset materials, requires specialised manufacturing methods.…”
Section: Introductionmentioning
confidence: 99%